2016
DOI: 10.1002/2016jd024892
|View full text |Cite
|
Sign up to set email alerts
|

The paleoclimate context and future trajectory of extreme summer hydroclimate in eastern Australia

Abstract: Eastern Australia recently experienced an intense drought (Millennium Drought, 2003–2009) and record‐breaking rainfall and flooding (austral summer 2010–2011). There is some limited evidence for a climate change contribution to these events, but such analyses are hampered by the paucity of information on long‐term natural variability. Analyzing a new reconstruction of summer (December–January–February) Palmer Drought Severity Index (the Australia‐New Zealand Drought Atlas; ANZDA, 1500–2012 Common Era), we find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 99 publications
5
30
0
Order By: Relevance
“…In the much longer context of our rainfall reconstruction, 2010-2011 was one of the wettest warm seasons in the past several centuries, not only in Murray Basin but also in Monsoonal North, Rangelands, Southern Slopes and East Coast. Cook et al (2016) found similar results based on the ANZDA reconstruction of spatial variability in the PDSI. The 1979-1983 period of dry conditions in eastern Australia and the 1983 warm season and 1984 coolseason wet anomalies in the East Coast, Wet Tropics and Monsoonal North are also captured in the reconstructions.…”
Section: Discussionsupporting
confidence: 73%
“…In the much longer context of our rainfall reconstruction, 2010-2011 was one of the wettest warm seasons in the past several centuries, not only in Murray Basin but also in Monsoonal North, Rangelands, Southern Slopes and East Coast. Cook et al (2016) found similar results based on the ANZDA reconstruction of spatial variability in the PDSI. The 1979-1983 period of dry conditions in eastern Australia and the 1983 warm season and 1984 coolseason wet anomalies in the East Coast, Wet Tropics and Monsoonal North are also captured in the reconstructions.…”
Section: Discussionsupporting
confidence: 73%
“…Despite the high incidence of antiphase hydroclimatic conditions, we find at least one period of extreme drought during the 1830s was synchronous between inland (north and south) western and eastern Australia in the last two centuries (Cook et al 2016b, Gallant and Gergis 2011, Ho et al 2015 figures 3(a)-(c)). This finding suggests it is possible that drought conditions were widespread across the continent during this period; however, a more precise understanding of the spatial signature of this drought period (and other past drought and wet periods) is contingent upon the development of an Australia-wide drought atlas.…”
Section: Past Hydroclimatic Variability In Inland Western Australiamentioning
confidence: 69%
“…For example, two of the three major drought periods in inland western Australia (i.e. 1880s and 1950s) coincided with relatively wet periods in south-eastern Australia (figures 3(a)-(d); Cook et al 2016b. In fact, the 1950s drought in western Australia coincided with the highest decadal-scale stream flow of the Murray River (in south-eastern Australia) in the last 200 years (Gallant and Gergis 2011).…”
Section: Past Hydroclimatic Variability In Inland Western Australiamentioning
confidence: 92%
“…As a dry and inhabited continent on Earth and with high streamflow variability, Australia is particularly prone to large-scale changes in hydroclimatic conditions (Cook et al, 2016;Verdon et al, 2004;Westra & Sharma, 2006;Zhang et al, 2016c). Meanwhile, flooding is one of the most severe natural disasters in Australia, with consequent impacts on many natural and social sectors (FitzGerald et al, 2010;Noji, 1995).…”
Section: Introductionmentioning
confidence: 99%